2020
DOI: 10.3892/ol.2020.11730
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiles that underpin the preventive and therapeutic potential of Moringa oleifera Lam against azoxymethane and dextran sodium sulfate‑induced mouse colon carcinogenesis

Abstract: Previous studies in a mouse model have indicated the anticancer potential of boiled Moringa oleifera pod (bMO)-supplemented diets; however, its molecular mechanisms are still unclear. Therefore, the present study aimed to explore the protein expression profiles responsible for the suppressive effect of bMO supplementation on azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced mouse colon carcinogenesis. Analysis by gel electrophoresis and liquid chromatography-tandem mass spectrophotometry demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In this study, membrane proteomic analysis was conducted on the intestinal mucosa from an AOM/DSS-induced mouse model of colon cancer. Although previous proteomic studies utilizing the AOM/DSS mouse model have explored proteins related to colon cancer [32][33][34][35][36][37], membrane proteomic studies are limited, hindering the investigation of lower abundance and insoluble membrane proteins. In this study, membrane proteomic analysis revealed the regulation of metabolic pathways in tumor tissues compared with that in the adjacent normal colon tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, membrane proteomic analysis was conducted on the intestinal mucosa from an AOM/DSS-induced mouse model of colon cancer. Although previous proteomic studies utilizing the AOM/DSS mouse model have explored proteins related to colon cancer [32][33][34][35][36][37], membrane proteomic studies are limited, hindering the investigation of lower abundance and insoluble membrane proteins. In this study, membrane proteomic analysis revealed the regulation of metabolic pathways in tumor tissues compared with that in the adjacent normal colon tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Te ethanolic extracts were associated with signifcant normalization of proteins of antioxidant, antiinfammatory, and antiapoptotic activities [197]. Mass spectrometric results revealed that there was a modulation in the expression of about 125 proteins included in metabolism, signal transduction, transcription, and translation in models supplemented with pods [198]. MO extracts also have been shown to introduce protection against apoptosis and oxidative stress induced in human neuroblastoma cells through their ability to activate caspase-3 [199].…”
Section: Moringa Oleifera and Proteinsmentioning
confidence: 99%
“…PPM1G promotes the activity of viral and cellular transcription factors such as HIV Tat and NF-κB [42][43][44] . PPM1G regulates alternative splicing [45][46][47] , in ammatory responses and cancer development 42,43,[47][48][49][50][51][52][53] . PPM1G was reported to dephosphorylate 4E-BP1 54 , which is the predominant eIF4E binding protein in most tissues, with brain as a notable exception 55 .…”
Section: Introductionmentioning
confidence: 99%